Low-density high-modulus high-bending-resistance rigid polyurethane foam as well as preparation method and application thereof
Through the molecular structure design and the use of chain extenders with suspended chains of different lengths, low-density, high-modulus, high-bending and rigid polyurethane foam was prepared, which solved the problem of insufficient bending performance of existing foams, and achieved the improvement of high strength, lightweight and moisture-proof performance. It is suitable for a variety of large-scale structural materials applications.
Patent Information
- Application Number
- CN202411973544.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The existing low-density rigid polyurethane foam has poor bending strength and flexural modulus performance, making it difficult to meet the high strength and lightweight needs of aircraft, ships and other large structural materials.
Through molecular structure design, a chain extender with different lengths of suspension chains is used to introduce suspended chains with different carbon chain lengths and polar groups into the hard section of the polyurethane to prepare low-density, high modulus, and high flexural resistance rigid polyurethane foam.
It has achieved low density, high bending performance, and excellent moisture resistance. It has good toughness, impact resistance and damping performance. It is suitable for aerospace, ship manufacturing, military vehicles and protective equipment and other fields.
Smart Images

Figure CN119775525A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of advanced material synthesis, and in particular relates to a low-density, high-modulus, high-bending-resistance rigid polyurethane foam, and a preparation method and application thereof. Background Art
[0002] Polyurethane Rigid Foam (PUR) is a porous structure material generated by chemical reaction with polyol and isocyanate as the main reactants. This material has the characteristics of low density, high strength, excellent thermal insulation performance, good mechanical properties and compressive strength. Rigid polyurethane foam can be customized according to its density, hardness, structure and purpose, and is widely used in aerospace, ocean transportation, protective equipment and other fields.
[0003] Nowadays, the development of aircraft has a great demand for structural lightweighting and strength improvement. When used as a structural material, the foam body needs to withstand a large mechanical load. Improving its bending strength and bending modulus can improve the strength of the overall structure of the aircraft, and improve the stability and deformation resistance of the aircraft while ensuring lightweight; high bending performance helps to improve the aircraft's fatigue resistance to repetitive loads during long-term flight, effectively delaying material fatigue damage, and ensuring the reliability and safety of the aircraft. In the field of ship structural materials, the use of low-density, high-bending performance materials as hull core materials can effectively reduce the weight of the hull, while resisting the impact of wind and waves at sea and the effect of loads, ensuring navigation safety and transportation efficiency. In buoyancy and emergency life-saving devices, such as life rafts, buoyancy cabins, etc., low density and high bending performance can enable them to maintain their shape and function for a long time, providing long-term protection.
[0004] Therefore, improving the bending strength and bending modulus of polyurethane foam is an important direction to enhance the mechanical properties of foam and broaden its application field. However, for low-density rigid polyurethane foam, its bending strength and bending modulus are poor. In order to improve its bending performance, domestic and foreign scholars and researchers have adopted a variety of approaches. The most direct method is to increase the density of the foam, which can effectively improve the rigidity of the foam and reduce the deformation under bending load, but it will increase the weight of the foam, reduce the thermal insulation performance, and is not conducive to lightweight applications. Fillers such as glass fiber, carbon fiber and carbon nanotubes are also commonly used, but the addition of fillers will lead to uneven material dispersion during the foaming process, difficult molding, increased material density, and increased brittleness. There is also an adjustment of the ratio between the soft and hard segments in the foam, increasing the content of the hard segment, and improving its rigidity and strength, but it will also sacrifice the flexibility and crack resistance of the foam, making it brittle, and the brittleness phenomenon is more obvious at low temperatures.
[0005] Therefore, it is very important to find a process for preparing low-density rigid polyurethane foam with excellent bending properties that can be used as a large-scale structural material. Summary of the invention
[0006] In view of the defects of the prior art, the present invention provides a modified polyurethane material and a preparation method thereof, the purpose of which is to prepare a rigid polyurethane foam with low density and excellent bending properties that can be used as a large structural material.
[0007] The present invention provides a low-density, high-modulus, high-bending-resistance rigid polyurethane foam, which is prepared by using the following raw materials in parts by weight:
[0008] 95-150 parts of polyether polyol,
[0009] Chain extender 7-36 parts,
[0010] 5-30 parts of cross-linking agent,
[0011] 0.5-4 parts of foaming agent,
[0012] Isocyanate 150-300 parts.
[0013] Preferably, the chain extender is selected from at least one of 1,2-propylene glycol, ethylene glycol, 1,2-pentanediol, 1,2-octanediol, 1,2-tetradecanediol, and stearic acid monoglyceride.
[0014] Preferably, the chain extender is 1,2-propylene glycol.
[0015] Preferably, the isocyanate index R is 1 to 1.25.
[0016] Preferably, the polyether polyol is selected from 4110 polyether polyol, 8345 polyether polyol, 2490 polyether polyol; the cross-linking agent is selected from glycerol, diethanolamine, triethanolamine, and the foaming agent is water;
[0017] And / or, the isocyanate is polyphenyl polymethylene polyisocyanate.
[0018] The present invention provides a low-density, high-modulus, high-bending-resistance rigid polyurethane foam as described in any one of the above items, which is prepared by a method comprising the following steps:
[0019] Step 1, mixing polyether polyol with a chain extender, a cross-linking agent, and a foaming agent to prepare a polyol mixture;
[0020] Step 2, isocyanate reacts with the polyol mixture and ages to obtain a product.
[0021] Preferably, in step 1, the mixing is mixing polyether polyol with a chain extender, a cross-linking agent, a foaming agent, a foam stabilizer, an amine catalyst and an antioxidant;
[0022] The foam stabilizer is S-6920 foam stabilizer; and / or, the amine catalyst is 2040 catalyst; and / or, the antioxidant is pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate.
[0023] Preferably, the weight ratio of polyether polyol to foam stabilizer, amine catalyst and antioxidant is 95-150:0.5-5:0.1-1:0.5-4.
[0024] Preferably, in step 1, the mixing is stirring at a speed of 2800 to 7000 r / min for 30 to 80 s;
[0025] And / or, in step 2, the reaction is that isocyanate is added to the polyol mixture, stirred at a speed of 2800 to 7000 r / min for 20 to 25 seconds, and the uniformly mixed material is poured into a mold and foamed for 180 to 400 seconds;
[0026] And / or, in step 2, the aging is curing at 20-25° C. for 20-26 hours.
[0027] The present invention also provides a method for preparing the low-density, high-modulus, high-bending-resistance rigid polyurethane foam described in any one of the above items, comprising the following steps:
[0028] Step 1, mixing polyether polyol with a chain extender, a cross-linking agent, and a foaming agent to prepare a polyol mixture;
[0029] Step 2, mixing the isocyanate with the polyol mixture and aging the mixture.
[0030] The present invention also provides the use of the low-density, high-modulus, high-bending-resistance rigid polyurethane foam described in any one of the above items as a material in the fields of aerospace, shipbuilding, military vehicles and protective equipment, and automobiles.
[0031] The present invention provides a low-density, high-modulus, high-bending rigid polyurethane foam. Through molecular structure design, chain extenders with hanging chains of different lengths are used to introduce hanging chains with polar groups of different carbon chain lengths into the polyurethane hard segment, so as to prepare a series of polyurethane materials. The polyurethane material has low density, high bending performance, and excellent moisture resistance. Among them, the polyurethane material prepared by using 1,2-propylene glycol as a chain extender has more excellent performance. The polyurethane material also has good toughness, impact resistance, good damping performance and good stability, showing development potential in the fields of aerospace, shipbuilding, military vehicles and protective equipment, and the automotive industry, and has good application prospects.
[0032] The present invention uses only chain extenders with different length segments and polar groups as pendant chains and isocyanates of specific structures as raw materials, which will not cause a sudden increase in density and affect lightweight applications. Compared with other solutions, the production process of the present invention is significantly simpler, does not require the addition of dispersants, modifiers, and does not use ultrasonic dispersion equipment. Compared with other solutions, the production process is simpler, the production efficiency is higher, it is suitable for large-scale preparation, and has good industrial application value.
[0033] The present invention does not introduce fillers with a density much greater than that of the polyurethane matrix only through molecular structure design, and will not cause a sudden increase in foam density. At the same time, the one-step molding technology used in this solution has a simple process and does not require a foam precursor and pre-foaming stage. Compared with other solutions, the production process is significantly simpler, the production efficiency is higher, the product can be adjusted in a wider range, and it has more industrial application value. Combined with all-water foaming technology, fewer auxiliary materials and additives are used, which reduces the generation of waste and pollutants in the production process. The less residues and harmful gases generated are also beneficial to environmental protection and meet the current needs of green production.
[0034] Compared with adding reinforcing materials to polyurethane foam, the present invention does not need to add coupling agents or surface treat the materials, and does not increase the process complexity and production cost. From the comparison of adding more isocyanates, replacing high-functionality polyether polyols, etc., first of all, replacing high-functionality polyether polyols will cause the viscosity of the polyether polyol itself to be too high, and even pre-cooling treatment in advance cannot significantly reduce its viscosity, which will bring difficulties to the processability and formability of polyurethane foam. Adding more isocyanates, the isocyanate index currently used basically guarantees the full progress of the reaction. Although adding more isocyanates can increase the hard segment ratio and thus increase the degree of crosslinking, it also severely restricts the movement of the chain segments, causing the foam to become brittle, and its bending strength and impact toughness decrease. In terms of catalysts, excessive use of catalysts will make the foaming reaction and gel reaction rate inconsistent, ultimately leading to: uneven foam structure; excessive foam pores, forming defects; shrinkage or cracking of the foam surface; gas overflow, foam collapse; unstable production process, poor batch stability and other results.
[0035] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0036] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The present invention is a flow chart for the preparation of low-density, high-modulus and high-bending-resistance rigid polyurethane foam. DETAILED DESCRIPTION
[0038] In the following examples and experimental examples, reagents and materials not particularly described are all commercially available.
[0039] In the following examples, different chain extenders were selected, and the amount of the chain extender was converted according to the hydroxyl value parameter.
[0040] Example 1 A modified rigid polyurethane foam material and a preparation method thereof
[0041] The modified polyurethane material of this embodiment is prepared by Figure 1 The method shown is used to prepare:
[0042] First, place the 4110 polyether polyol in a refrigerator at 5°C for 24 hours. Then, add 100g of 4110 polyether polyol, 7.35g of 1,2-propylene glycol, 9g of propylene glycol, 1.0g of water, 2.1g of S-6920 foam stabilizer, 0.4g of 2040 catalyst, and 1.85g of pentaerythritol tetra(3,5-di-tert-butyl-4-hydroxy)phenylpropionate to the container. The agitator stirs at 3000r / min for 75s to allow the polyether polyol mixture to be fully mixed. Weigh 189.34g of polyphenyl polymethylene polyisocyanate, with an isocyanate index R of 1.05. After stirring, quickly add the isocyanate to the polyol mixture and stir at 3000r / min for 20-25s. Finally, the mixed composite material was poured into a mold for foaming, which lasted for 232 seconds. After the foaming process was completed, the composite material was aged at room temperature for 24 hours and then taken out for use.
[0043] Example 2 A modified rigid polyurethane foam material and a preparation method thereof
[0044] The method of Example 1 is followed, except that the amount of 1,2-propylene glycol used is 7.36 g, the amount of polyphenyl polymethylene polyisocyanate used is 193.97 g, and the foaming duration is 237 s.
[0045] Example 3 A modified rigid polyurethane foam material and its preparation method
[0046] The method of Example 1 is followed, except that 7.35 g of 1,2-propylene glycol is replaced by 6 g of ethylene glycol, the amount of polyphenyl polymethylene polyisocyanate used is 190.87 g, and the foaming duration is 226 s.
[0047] Example 4 A modified rigid polyurethane foam material and its preparation method
[0048] The method of Example 1 is followed, except that 7.35 g of 1,2-propylene glycol is replaced by 10.1 g of 1,2-pentanediol, the amount of water used is 0.9 g, the amount of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)benzene propionate used is 1.84 g, the amount of polyphenyl polymethylene polyisocyanate used is 185.21 g, and the foaming duration is 204 s.
[0049] Example 5 A modified rigid polyurethane foam material and its preparation method
[0050] The method of Example 1 is followed, except that 7.35 g of 1,2-propylene glycol is replaced by 14 g of 1,2-octanediol, the amount of water is 0.9 g, the amount of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropanoate is 1.84 g, the amount of polyphenylpolymethylene polyisocyanate is 189.76 g, and the foaming duration is 220 s.
[0051] Example 6 A modified rigid polyurethane foam material and its preparation method
[0052] The method of Example 1 is followed, except that 7.35 g of 1,2-propylene glycol is replaced by 11.45 g of 1,2-tetradecanediol, the amount of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)benzene propionate is 1.80 g, the amount of polyphenyl polymethylene polyisocyanate is 19.07 g, and the foaming duration is 323 s.
[0053] Example 7 A modified rigid polyurethane foam material and its preparation method
[0054] The method of Example 1 is followed, except that 7.35 g of 1,2-propylene glycol is replaced by 35.60 g of stearic acid monoglyceride, the amount of water is 1.30 g, the amount of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate is 1.84 g, the amount of polyphenylpolymethylene polyisocyanate is 196.15 g, and the foaming duration is 335 s.
[0055] Example 8 A modified rigid polyurethane foam material and its preparation method
[0056] The method of Example 1 is followed, except that the amount of polyether polyol used is 150 g, the amount of propylene glycol used is 30 g, the amount of water used is 4 g, the stirrer is stirred at a speed of 7000 r / min for 30 seconds, and the amount of isocyanate used is 300 g.
[0057] The technical solution of the present invention is further illustrated by experiments below.
[0058] In the following experimental examples, the tested materials were respectively rigid polyurethane foam materials prepared according to the methods described in Examples 1-7.
[0059] Experimental Example 1 Characterization of Density, Bending Strength and Bending Modulus of Polyurethane Materials
[0060] 1. Experimental Methods
[0061] 1. Determination of density
[0062] According to GB / T 6343-2009, after removing the surface skin, the foam is cut into standard cubic samples with a size of 30mm×30mm×30mm. Take 8 samples at random, measure the length, width and height of the samples with a vernier caliper to an accuracy of 0.02mm, and then weigh the mass of the foam samples with an analytical balance. The ratio of the sample mass to the sample volume is the apparent core density of the polyurethane foam.
[0063] 2. Determination of flexural strength and flexural modulus
[0064] Bending strength, refer to GB8812.1-2007 "Determination of flexural properties of rigid foam plastics Part 1: Basic bending test" for sample preparation, sample size 120mm×25mm×20mm, span 100mm, test speed 10mm / min. Record its load-strain curve, when the sample is less than 5% strain, record the breaking load. Calculation of bending strength and bending modulus refers to GBT8812.2-2007 "Determination of bending strength and apparent bending elastic modulus".
[0065] 2. Experimental Results
[0066] The results of density, bending strength and bending modulus are shown in Table 1: According to the method in the above embodiment, only the chain extender with hanging chains is changed, and the density of the modified polyurethane material prepared is basically unchanged, or slightly changed; the polyurethane material using 1,2-propylene glycol as a chain extender has a bending strength and bending modulus that are significantly greater than those prepared by other chain extenders, especially those prepared by chain extenders with longer carbon chains and greater side chain steric hindrance. The results show that using 1,2-propylene glycol as a chain extender, according to the experimental scheme of the present invention, a rigid polyurethane foam material with low density, high bending strength and high bending modulus can be obtained. When other diols are used as chain extenders, their bending strength and bending modulus are lower than those of the rigid foam material prepared by 1,2-propylene glycol.
[0067] Table 1 Determination results of density, flexural strength and flexural modulus
[0068]
[0069] Experimental Example 2 Characterization of other properties of polyurethane materials
[0070] 1. Experimental Methods
[0071] 1. Determination of compressive strength and modulus
[0072] Test compressive strength and compressive modulus: refer to GB 8813-2020 "Determination of compression properties of rigid foam plastics", the sample size is 30mm×30mm×30mm, and the compression rate is 3mm / min. The yield strength is selected as the compressive strength, and according to the derived displacement-force curve, the tangent at the maximum slope of the curve is selected, and its corresponding value is the compression modulus.
[0073] 2. Determination of impact strength
[0074] According to GB / T 1043.1-2008 "Determination of impact properties of plastic simply supported beams", the unnotched simply supported beam impact test was carried out, the sample size was 120mm×15mm×10mm, the test span was 70mm, the test pendulum was 2J, and the speed was 2.9mm / s. The fracture strength was selected as the impact strength.
[0075] 3. Determination of loss factor Tanδ at 25℃
[0076] Use a vernier caliper to measure the size of the sample, take the average value of multiple position measurements, and record it on the dynamic mechanical analyzer (DMA). Mode selection on the dynamic mechanical analyzer: static load control is controlled by the contact force size, the contact force is 0.1N, the proportional factor is 1.3, and the static strain limit is 1%. Dynamic load control is deformation control, the dynamic deformation is 0.03mm, the dynamic force limit is 20N, the alternating load is none, and the load frequency is 1Hz. Liquid nitrogen refrigeration is selected for atmospheric conditions, and the purge gas is turned on. Maintain a heating rate of 5K / min, increase the temperature from 0℃ to 230℃, and keep warm for 300s. The equipment will record the data of its tanδ changing with temperature in real time. Save the parameters, name the file, and run the program. After completing the experiment, export the data and find the tanδ value at 25℃. Take the average of multiple samples.
[0077] 4. Determination of non-stick time S
[0078] Test non-stick time: According to the definition of various foaming reaction characteristic parameters, test conditions and test methods in HG / T 4574-2014 "Determination method of foaming reaction characteristics of polyurethane raw materials", non-stick time and other parameters are measured. That is, the time from the beginning of material mixing to the time when the gloved finger or glass rod touches the foam surface without sticking.
[0079] 5. Determination of water absorption
[0080] Select a sample of 150mm×150mm×30mm, and obtain the dry weight m1 and foam volume v by measurement. Immerse the sample in water, and remove bubbles on the surface of the sample with a soft brush or by stirring. Weigh again after 24 hours to obtain the wet weight m2. Water absorption rate = (m2-m1) / v.
[0081] 2. Experimental Results
[0082] The results of other mechanical properties are shown in Table 2: The rigid polyurethane foams prepared by the present invention all have high compressive strength, compressive modulus and impact strength. This shows that these rigid polyurethane foams have strong bearing capacity, good rigidity, and show good toughness and impact resistance, thus having the potential to be used in building structures, supporting parts, protective materials, packaging materials, precision instrument parts, etc.
[0083] Table 2 Determination results of other mechanical properties
[0084]
[0085]
[0086] The results of other properties are shown in Table 3: The loss factor of the rigid polyurethane foam prepared by the present invention is large, indicating that it has good damping performance and can effectively absorb and dissipate vibration energy. With the different types of chain extenders used, the results of the non-stick time of the rigid polyurethane foam are different, but the overall non-stick time is longer, indicating that the stability of the rigid polyurethane foam is better and can provide more time for subsequent processing. With the different types of chain extenders used, the results of the water absorption rate of the rigid polyurethane foam are also different. Except for ethylene glycol, the rigid polyurethane foam prepared by other chain extenders has a lower water absorption rate as the chain length becomes shorter, indicating that the rigid polyurethane foam prepared by 1,2-propylene glycol has good moisture resistance and can maintain good performance in a humid environment. It has excellent durability and provides buoyancy performance. The results show that the rigid polyurethane foam prepared by the present invention has good damping performance, low water absorption, good impact resistance, and exhibits excellent adaptability and stability. Among them, the rigid polyurethane foam prepared by 1,2-propylene glycol as a chain extender has the best moisture resistance.
[0087] Table 3 Determination results of other properties
[0088]
[0089] The above results show that the rigid polyurethane foam prepared by the present invention also has high compressive strength, high compressive modulus and high impact strength, good damping performance, long non-stick time and good moisture resistance, among which the rigid polyurethane foam material prepared with 1,2-propylene glycol has excellent properties, especially moisture resistance. Therefore, the rigid polyurethane foam prepared by the present invention has excellent properties and has the potential to be used in the fields of aerospace, shipbuilding, military vehicles and protective equipment, and the automotive industry.
[0090] It can be seen from the above embodiments and experimental examples that the present invention provides a low-density, high-modulus, high-bending rigid polyurethane foam. Through molecular structure design, chain extenders with hanging chains of different lengths are used to introduce hanging chains with different carbon chain lengths and polar groups into the polyurethane hard segment, and a series of polyurethane materials are prepared. During the preparation process of these materials, there is no need to add reinforcing materials, coupling agents or surface treatment of the materials, nor is there any need to use too much isocyanate or replace high-functionality polyether polyols. The polyurethane material has low density, high bending performance, and excellent moisture resistance. Among them, the polyurethane material prepared with 1,2-propylene glycol as a chain extender has better performance. The polyurethane material also has good toughness, impact resistance, good damping performance and good stability, showing development potential in the fields of aerospace, shipbuilding, military vehicles and protective equipment, and the automotive industry, and has good application prospects.
Claims
1. A low-density, high-modulus, high-bending-resistance rigid polyurethane foam, characterized in that: The invention is prepared by using the following raw materials in parts by weight: 95-150 parts of polyether polyol, Chain extender 7-36 parts, 5-30 parts of cross-linking agent, 0.5-4 parts of foaming agent, Isocyanate 150-300 parts.
2. The low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to claim 1, characterized in that: The chain extender is selected from at least one of 1,2-propylene glycol, ethylene glycol, 1,2-pentanediol, 1,2-octanediol, 1,2-tetradecanediol, and stearic acid monoglyceride.
3. The low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to claim 2, characterized in that: The chain extender is 1,2-propylene glycol.
4. The low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to claim 1, characterized in that: The isocyanate index R is 1 to 1.
25.
5. The low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to claim 1, characterized in that: The polyether polyol is selected from 4110 polyether polyol, 8345 polyether polyol, and 2490 polyether polyol; the cross-linking agent is selected from glycerol, diethanolamine, and triethanolamine; and the foaming agent is water; And / or, the isocyanate is polyphenyl polymethylene polyisocyanate.
6. The low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to any one of claims 1 to 5, characterized in that: It is prepared by a method comprising the following steps: Step 1, mixing polyether polyol with a chain extender, a cross-linking agent, and a foaming agent to prepare a polyol mixture; Step 2, isocyanate reacts with the polyol mixture and ages to obtain a product.
7. The low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to claim 6, characterized in that: In step 1, the mixing is mixing polyether polyol with a chain extender, a cross-linking agent, a foaming agent, a foam stabilizer, an amine catalyst and an antioxidant; The foam stabilizer is S-6920 foam stabilizer; and / or, the amine catalyst is 2040 catalyst; and / or, the antioxidant is pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate.
8. The low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to claim 7, characterized in that: The weight ratio of the polyether polyol to the foam stabilizer, the amine catalyst and the antioxidant is 95-150:0.5-5:0.1-1:0.5-4.
9. The method for preparing the low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to any one of claims 1 to 8, characterized in that: The steps include: Step 1, mixing polyether polyol with a chain extender, a cross-linking agent, and a foaming agent to prepare a polyol mixture; Step 2, mixing the isocyanate with the polyol mixture and aging the mixture.
10. Use of the low-density, high-modulus, high-bending-resistance rigid polyurethane foam according to any one of claims 1 to 8 as a material in the fields of aerospace, shipbuilding, military vehicles and protective equipment, and automobiles.
Citation Information
Patent Citations
Degradation resistance fire retardation type rigid polyurethane foam material and preparation method thereof
CN102977586A
Low-density high-strength polyurethane foam as well as preparation method and application thereof
CN113248681A
Low density polyurethane foams
CN119053635A
Rigid polyurethane foam
JP1999080307A
Method of manufacturing polyurethane foam
JP2009057485A